Experimental investigation on an integrated thermal management system with heat pipe heat exchanger for electric vehicle. (15th June 2016) - Zou, Huiming; Wang, Wei; Zhang, Guiying; Qin, Fei; Tian, Changqing; Yan, Yuying
Highlights: An integrated thermal management system is proposed for electric vehicle. The parallel branch of battery chiller can supply additional cooling capacity. Heat pipe performance on preheating mode is better than that on cooling mode. Heat pipe heat exchanger is a feasible choice for battery thermal management. Abstract: An integrated thermal management system combining a heat pipe battery cooling/preheating system with the heat pump air conditioning system is presented to fulfill the comprehensive energy utilization for electric vehicles. A test bench with battery heat pipe heat exchanger and heat pump air conditioning for a regular five-chair electric car is set up to research the performance of this integrated system under different working conditions. The investigation results show that as the system is designed to meet the basic cabinet cooling demand, the additional parallel branch of battery chiller is a good way to solve the battery group cooling problem, which can supply about 20% additional cooling capacity without input power increase. Its coefficient of performance for cabinet heating is around 1.34 at −20 °C out-car temperature and 20 °C in-car temperature. The specific heat of the battery group is tested about 1.24 kJ/kg °C. There exists a necessary temperature condition for the heat pipe heat exchanger to start action. The heat pipe heat transfer performance is around 0.87 W/°C on cooling mode and 1.11 W/°C on preheating mode. The gravity role makes the heat transfer performance of the heat pipe on preheating mode better than that on cooling mode.